Estimation of Convergence Rate in the Transfer Theorem for Maxima - Aksomaitis, A. (Nonlinear Analysis: Modelling and Control, 2008)
Let ZN be a maximum of independent identically distributed random variables. In this paper, a nonuniform estimate of convergence rate in the transfer theorem max-scheme is obtained. Presented results make the estimates, given in [1] and [2], more precise.
Keywords: max-scheme; transfer theorem; limit theorem; rate of convergence